The solution to the equation is x = 1.62
<h3>How to solve the equation?</h3>
The equation is given as:
![x =\sqrt{x\ -\ \frac{1}{x}}+\sqrt{1-\ \frac{1}{x}}](https://tex.z-dn.net/?f=x%20%3D%5Csqrt%7Bx%5C%20-%5C%20%5Cfrac%7B1%7D%7Bx%7D%7D%2B%5Csqrt%7B1-%5C%20%5Cfrac%7B1%7D%7Bx%7D%7D)
Next, we split the equations as follows:
y = x
![y =\sqrt{x\ -\ \frac{1}{x}}+\sqrt{1-\ \frac{1}{x}}](https://tex.z-dn.net/?f=y%20%3D%5Csqrt%7Bx%5C%20-%5C%20%5Cfrac%7B1%7D%7Bx%7D%7D%2B%5Csqrt%7B1-%5C%20%5Cfrac%7B1%7D%7Bx%7D%7D)
Next, we graph the equations (see attachment)
From the attached graph, the equations intersect at
(x, y)= (1.62, 1.62)
Remove the y value
x = 1.62
Hence, the solution to the equation is x = 1.62
Read more about equations at
brainly.com/question/2972832
#SPJ1